1984
DOI: 10.1080/15287398409530601
|View full text |Cite
|
Sign up to set email alerts
|

Relative effects of asbestos and wollastonite on alveolar macrophages

Abstract: Rabbit alveolar macrophages were exposed in culture to chrysotile asbestos, wollastonite, or latex, and the effects on various biochemical and physiological parameters related to cellular viability and fibrogenicity were determined. Exposure of alveolar macrophages to asbestos, wollastonite, or latex for 3 d has no effect on oxygen consumption or cellular volume. However, treatment of alveolar macrophages with as little as 25 micrograms asbestos/ml for 1 d increases lysosomal enzyme release and decreases membr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
1

Year Published

1995
1995
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 19 publications
0
8
1
Order By: Relevance
“…By counts under phasecontrast microscopy, there were 200 x 106 fibers/g. Wollastonite, a relatively nonpathogenic calcium silicate fiber in both in vitro (18) and in vivo (19) studies, was used as a control fiber. The preparation of wollastonite used was Nyglos I (or Rimglos), milled to a geometry mimicking that of crocidolite asbestos (mean length 12 tm, range 2-80 tm, mean width 2 Am) (NYCO Minerals, Willsboro, NY).…”
Section: Methodsmentioning
confidence: 99%
“…By counts under phasecontrast microscopy, there were 200 x 106 fibers/g. Wollastonite, a relatively nonpathogenic calcium silicate fiber in both in vitro (18) and in vivo (19) studies, was used as a control fiber. The preparation of wollastonite used was Nyglos I (or Rimglos), milled to a geometry mimicking that of crocidolite asbestos (mean length 12 tm, range 2-80 tm, mean width 2 Am) (NYCO Minerals, Willsboro, NY).…”
Section: Methodsmentioning
confidence: 99%
“…However, chronic inhalation of fiberglass in rats resulted in neither pulmonary fibrosis nor cancer (Hesterberg et al, 1993). In contrast, an in vitro assay system has been able to verify epidemiological data suggesting that wollastonite is less pathogenic than asbestos (Pailes et al, 1984).…”
Section: Please Scroll Down For Articlementioning
confidence: 95%
“…These agents may directly damage the lung parenchyma, as well as recruit and activate other cells (e.g., neutrophils and fibroblasts) that are important in alveolitis and the development of fibrosis. In our laboratory, alveolar macrophage cultures have proven to be an accurate system to evaluate the toxicity of chrysotile asbestos and wollastonite (Pailes et al, 1984); chrysotile was determined to be toxic, while wollastonite was deemed far less toxic and latex beads were found to be nontoxic. These in vitro results correlate with the epidemiological finding of Shasby et al (1979) that wollastonite is nontoxic to exposed workers.…”
Section: Please Scroll Down For Articlementioning
confidence: 99%
See 1 more Smart Citation
“…Generally speaking, these studies indicated that wollastonite caused cellular level effects, but these were less than those observed with various types of asbestos. For example, Pailes et al (1984) exposed cultures of rabbit alveolar macrophages to chrysotile, wollastonite (NYCO Minerals, 98% ≤8µm length), and latex beads at concentrations ranging from 50 to 250 µg/ml. The authors found that chrysotile was cytotoxic whereas wollastonite was far less cytotoxic.…”
Section: Other Studiesmentioning
confidence: 99%